The Effect of Service Quality and Promotion on Purchasing Decisions that Impact Consumer Loyalty in Using VIT Bottled Water Production by PT. Tirta Varia Intipratama in Bandung Region - Heri Erlangga (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
This study aims to determine the effect of service quality and promotion on purchasing decisions that have an impact on consumer loyalty in using VIT bottled water produced by PT Turta Varia Intipratama in the Bandung Region. The method used is explanatory research with a sample of 96 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study show that service quality has a significant effect on purchasing decisions by 31.6%, hypothesis testing obtained a significance of 0.000 <0.05. Promotion has a significant effect on purchasing decisions by 46.6%, hypothesis testing obtained a significance of 0.000 <0.05. Service quality and promotion simultaneously have a significant effect on purchasing decisions by 51.9%, hypothesis testing obtained a significance of 0.000 <0.05. Purchase decisions have a significant effect on consumer loyalty by 31.2%, hypothesis testing obtained a significance of 0.000 <0.05.